Revolutionizing Neonatal Care: A Comprehensive Assessment of Neuromotor Development in At-Risk Infants Using the Novel Neonatal Infant Motor Assessment Scale (NIMAS) Test Battery - Mustafa Ali Akin; Nilay Comuk Balci; Mert Demirsoz (MDPI AG, 2024)
We developed a new neonatal neuromotor test battery, the Neonatal Infant Motor Assessment Scale (NIMAS), to perform a detailed neuromotor and holistic assessment of at-risk infants in the neonatal period. Methods: A total of 68 infants (28-41 Gestational weeks) hospitalised in the Neonatal Intensive Care Unit were included in the study. The NIMAS is a scale consisting of Automatic Motor Area, Functional Motor Area and sociodemographic form. The Dubowitz Neurological Examination and the Amiel-Tison Neurological Assessment Tests were also applied to evaluate the construct validity of the test. Results: The mean gestational age at birth was 34.62 ± 3.07 weeks and birth weight was 2305.66 ± 738.95. Fifty-one (75%) of the babies were premature and 17 (25%) were term babies. The KMO value to test the adequacy of the distribution for factor analysis was found to be at a very good level. Barlett's test result was 2198.389 (p < 0.05). The amount of variance obtained as 44.76% in the study was at a sufficient level. The factor loads of the questions in the automatic motor domain dimension varied between 0.523 and 0.694 and the factor loads of the questions in the functional motor domain dimension varied between 0.619 and 0.772. Since Cronbach's alpha was above 0.70, the reliability was adequate. Inter-rater scale agreement in the automatic motor domain was 81.1%; scale agreement in the functional motor domFain was 92.9%; and the NIMAS total score agreement was 93.4%. These agreements were statistically significant (p < 0.05). Total correlation above 0.20 indicates that the item is important for the question. According to the results obtained, total correlation values were between 0.258 and 0.720. Conclusions: The NIMAS is the first test battery to assess the "Functional Motor Area" and this questionnaire, based on the results of the analyses, is a valid, reliable and clinically usable measurement tool for the infant at-risk at the neonatal period.